Claudin-3 and claudin-19 partially restore native phenotype to ARPE-19 cells via effects on tight junctions and gene expression. (October 2016) - Peng, Shaomin; Wang, Shao-Bin; Singh, Deepti; Zhao, Peter Y.C.; Davis, Katherine; Chen, Bo; Adelman, Ron A.; Rizzolo, Lawrence J.
Abstract: Mutations of claudin-19 cause severe ocular deficits that are not easily reconciled with its role in regulating the outer blood retinal barrier. ARPE-19 is a widely used culture model of the retinal pigment epithelium (RPE). ARPE-19 is unique among epithelial cell lines, because it expresses all tight junction proteins except claudin family members. ARPE-19 also loses aspects of the RPE phenotype with cell passage. This study asks whether exogenous expression of the main RPE claudins, claudin-3 and claudin-19, would restore RPE phenotype, and whether these claudins have distinct roles in RPE. An Ussing chamber was used to measure the transepithelial electrical resistance and transepithelial electrical potential. These measurements were used to estimate the permeability co-efficients of ions. The transepithelial diffusion of polyethylene glycols were used to examine the leak pathway of tight junctions. Wound-healing, quantitative RT-PCR and immunoblotting examined diverse aspects of the RPE phenotype. Over-expression of either claudin decreased the permeability of small ions and polyethylene glycol. Both claudins were slightly cation-specific, but claudin-3 was less permeable to large solutes. Claudin expression widely affected gene expression to partially restore RPE phenotype. Claudins redistributed filamentous actin from stress fibers to circumferential bands associated with tight junctions, and made wound-healing more epithelial-like. Both claudins increased the expression of genes related to RPE core functions and increased steady-state levels of phosphorylated-AKT. In conclusion, claudin-3 and claudin-19 formed general permeability barriers and affected cell morphology, proliferation, migration, AKT signaling, and gene expression. When claudins are exogenously expressed, ARPE-19 more closely model native RPE. Highlights: Expression of claudin-3 and -19, tight junction proteins of human RPE, helps restore native RPE phenotype to ARPE-19 cells. For ions, each claudin is general barrier protein that is slightly cation-specific. For large solutes, the leak pathway of tight junctions is greater for claudin-19 than claudin-3. Each claudin activates Akt, increases the expression of RPE-enriched mRNAs and restores epithelial-like wound-healing.